Dental signs attributed to congenital syphilis and its treatments in the Hamann-Todd Skeletal Collection - Ioannou, Stella; Henneberg, Maciej (Anthropological Review, 2017)
Syphilis in the United States during the 1800s and 1900s had a high prevalence rate causing great concern to health officials. Various measures were taken to control its spread. Mercuric treatments were used up until the introduction of penicillin. The aim of this paper is to determine whether dental abnormalities related to congenital syphilis in individuals who died of syphilis or syphilis-related causes, in the Hamman Todd Osteological Collection, occur and whether mercurial treatment was effective. Hutchinson, Moon and Fournier’s works were analyzed to determine dental abnormalities associated with congenital syphilis and its treatments and used as criteria. Hillson et al. (AJPA,107:25-40) standardized method of description of dental changes was used. In the Hamman Todd Osteological Collection in Cleveland, Ohio, 102 individuals had cause of death recorded in the catalogue as syphilis or lues, and 69 had causes of death relating to syphilis which included paresis (53), aortic insufficiency (15) and pericarditis (1). Thus altogether 171 individuals were studied. Dentition was examined to determine if dental abnormalities associated with congenital syphilis and its treatments were present in individuals not recorded as having congenital syphilis. Crania were examined for any osteological changes. One individual (2266) demonstrated dental malformations possibly related to the congenital disease itself, while three demonstrated dental abnormalities associated with mercuric treatments in childhood (2118, 2263 and 3097). No remarkable bone pathologies were evident on any skull. The use of pre-penicillin treatment of congenital syphilis may have been effective to maintain health into adulthood but not always in eradicating the infection. Effects of mercury on enamel formation and bone changes, need to be considered when making a differential diagnosis of syphilis/congenital syphilis.